Electrochemical dissolution behavior of IC21 nickel-based single crystal alloy under electrochemical machining conditions - LI Shun; LIU Weidong; ZHAO Yonghua; YUE Xiaoming (Cailiao gongcheng)
IC21 alloy， as a new Ni3Al-based single crystal superalloy， has become an ideal material for manufacturing a new generation of aero-engine turbine guide vanes due to its high melting point， excellent high-temperature performance， and creep resistance performance. However， turbine guide vanes have complex structures， such as deep holes and deep and narrow slots， which are difficult to be processed efficiently by traditional machining techniques. Electrochemical machining has become the main method for processing such complex structures due to its advantages， such as no tool loss， high material removal rate， and no cutting stress and thermal effect. This paper focuses on the electrochemical dissolution behavior of IC21 nickel-based single crystal alloy in NaCl and NaNO3 electrolytes. The electrochemical reaction characteristics of IC21 alloy in different electrolytes are analysed by linear scanning voltammetric polarisation curve measurements. In addition， the dissolution characteristics and selective dissolution phenomena of the alloy under different electrolytes and current densities are investigated by current efficiency measurements and surface micro-morphology analysis. It is shown that IC21 alloy exhibits typical passivation-super-passivation transition phenomena in both NaCl and NaNO₃ electrolytes， in which the oxide layer formed in NaNO3 electrolyte exhibits higher stability. Current efficiency measurements show that the dissolution efficiency of IC21 alloy is more stable in NaCl electrolyte， and the dissolution efficiency in NaNO3 electrolyte gradually decreases with the increase of the current density， which exhibits different characteristics from the traditional theory. The dissolution surface morphology analysis further reveals the existence of the selective dissolution phenomenon of IC21 alloy under ECM conditions， and its microscopic mechanism is discussed. Based on the above experimental results， a theoretical model of electrochemical dissolution of IC21 alloy under different electrolyte and current density conditions is established， which provides a theoretical basis for the development and application of ECM processes for IC21 alloy.